3,4-dichlorobenzyl methacrylate and ethyl methacrylate system: monomer reactivity ratios and determination of thermodynamic properties at infinite dilution by using inverse gas chromatography - Demirelli, K; Kaya, I; Coskun, M (Elsevier Sci Ltd, 2001)
Copolymers with various contents of 3,4-dichlorobenzyl methacrylate (BzMA) and ethyl methacrylate (EMA) were prepared in 1,4-dioxane solution using 2,2 ' -azobisisobutyronitrile (AIBN) as initiator at 60 degreesC. The copolymer compositions were determined by H-1 NMR analysis. The monomer reactivity ratios were calculated by both Fineman-Ross, and Kelen-Tudos methods. The monomer reactivity ratios were found to be r(BMA) = 0.521 +/- 0.019, r(EMA) = 0.847 +/- 0.221 (Kelen-Tudos) and r(BMA) = 0.677 +/- 0.008 r(EMA) = 1.117 +/- 0.209 (Fineman-Ross). The FT-IR, C-13 NMR spectra of the copolymers have been discussed. In all other samples thermal degradation proceeded in a single step. A slight increase in thermal stability of the copolymers was observed with increase in BzMA content. Some thermodynamic quantities such as the specific retention volumes, V-g(0), weight fraction activity coefficients of solute probes at infinite dilution, Ohm (infinity)(1), Flory-Huggins intereaction parameters, chi (infinity)(12), between polymers and solvents, the partial molar free energy, DeltaG(1)(infinity) the partial molar heat of mixing, DeltaH(1)(infinity), at infinite dilution were determined from the interactions of poly(BzMA-co-EMA) with alcohols, ketones, acetates, aromatics and n-alkanes by inverse gas chromatography method at 130-150 degreesC. All probes are non-solvent for poly(BzMA-co-EMA) (7:93%) and poly(BzMA-co-EMA) (87:13%) at 130-150 degreesC. (C) 2001 Elsevier Science Ltd. All rights reserved.
Keywords: monomer reactivity ratios; NMR; inverse gas chromatography